2021
DOI: 10.1002/jcp.30250
|View full text |Cite
|
Sign up to set email alerts
|

FAM201A knockdown inhibits proliferation and invasion of lung adenocarcinoma cells by regulating miR‐7515/GLO1 axis

Abstract: Lung adenocarcinoma (LUAD) is the most important histological type of lung cancer. We aimed to identify the role of long noncoding RNA family with sequence similarity 201‐member A (FAM201A) in the occurrence and development of LUAD. The expressions of FAM201A in LUAD tissues and cells were determined via reverse transcription‑quantitative polymerase chain reaction. The effects of FAM201A knockdown on LUAD cell malignant phenotypes were examined by cell counting kit‐8, 5‐ethynyl‐2’‐deoxyuridine, flow cytometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…For these patients, FAM201A-miR-370-EGFR was suggested as a key axis in regulation of radiotherapy sensitivity [ 34 ]. Another in vivo experiment showed that high level expression of FAM201A involved in development of lung adenocarcinoma and down-regulation of FAM201A exerted the opposite effect [ 35 ]. In addition to cancers, down-regulation of FAM201A was reported to be associated with Osteonecrosis of the femoral head through bioinformatics analysis and quantitative real-time polymerase chain reaction experiments [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these patients, FAM201A-miR-370-EGFR was suggested as a key axis in regulation of radiotherapy sensitivity [ 34 ]. Another in vivo experiment showed that high level expression of FAM201A involved in development of lung adenocarcinoma and down-regulation of FAM201A exerted the opposite effect [ 35 ]. In addition to cancers, down-regulation of FAM201A was reported to be associated with Osteonecrosis of the femoral head through bioinformatics analysis and quantitative real-time polymerase chain reaction experiments [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main functions of FAM201A is to regulate cell proliferation and invasion. Specifically, low expression of FAM201A can inhibit cell proliferation and invasion [ 35 ]. There is evidence that decreased cell proliferation and invasion are related to autophagy activation [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these patients, FAM201A-miR-370-EGFR was suggested a key axis in regulation of radiotherapy sensitivity [33]. Another in vivo experiment showed that high level expression of FAM201A involved in development of lung adenocarcinoma and down-regulation of FAM201A exerted the opposite effect [34]. In addition to cancers, down-regulation of FAM201A was reported to be associated with Osteonecrosis of the femoral head through bioinformatics analysis and quantitative real-time polymerase chain reaction experiments [35].…”
Section: Discussionmentioning
confidence: 99%
“…and invasion of cancer cells (10,12,13). However, the role of FaM10a in oa remains poorly understood.…”
Section: Positive Feedback Loop Of Lncrna Fam201a/mir-146a-5p/pou2f1 Regulates Il-1β-induced Chondrocyte Injury In Vitromentioning
confidence: 99%
“…A previous study demonstrated that expression levels of the lncRNA family with sequence similarity 201 member A (FAM201A) are decreased in necrotic femoral head samples ( 11 ). Whereas, FAM201A upregulation has been observed to promote the migration and invasion of cancer cells ( 10 , 12 , 13 ). However, the role of FAM10A in OA remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%